2015
DOI: 10.1002/jcsm.12062
|View full text |Cite
|
Sign up to set email alerts
|

Cachexia in chronic obstructive pulmonary disease: new insights and therapeutic perspective

Abstract: Cachexia and muscle wasting are well recognized as common and partly reversible features of chronic obstructive pulmonary disease (COPD), adversely affecting disease progression and prognosis. This argues for integration of weight and muscle maintenance in patient care. In this review, recent insights are presented in the diagnosis of muscle wasting in COPD, the pathophysiology of muscle wasting, and putative mechanisms involved in a disturbed energy balance as cachexia driver. We discuss the therapeutic impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 245 publications
(482 reference statements)
0
101
0
Order By: Relevance
“…It has been reported that FoxO1 and FoxO3 protein activity were unchanged in human cancer cachexia (61). Furthermore, in humans with chronic obstructive pulmonary disease, muscle atrophy is associated with an increase in Akt activation (17,57). These and several other data indicate that under certain conditions Akt/FoxO and atrogene activity can be independent of each other.…”
Section: Discussionmentioning
confidence: 81%
“…It has been reported that FoxO1 and FoxO3 protein activity were unchanged in human cancer cachexia (61). Furthermore, in humans with chronic obstructive pulmonary disease, muscle atrophy is associated with an increase in Akt activation (17,57). These and several other data indicate that under certain conditions Akt/FoxO and atrogene activity can be independent of each other.…”
Section: Discussionmentioning
confidence: 81%
“…1 The term sarcopenia, on the other hand, was coined in 1989 by Rosenberg and colleagues. [3][4][5] The diagnosis can be made by using weighing scale and by asking the patient for his or her weight before HF developed or 12 months before the actual date. Cachexia is frequent not only in patients with HF but also in patients with CKD, COPD, and neurological diseases as well as in rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Loss of oxidative type of muscle fibre, atrophy, and increased protein turnover are mechanisms explained for sarcopenia. 9 In a study done by Van Manen comorbidities were present in more than 50% of patients. 10 An interesting finding was only hypertension and history of tuberculosis was positively associated with COPD among 15 comorbidities.…”
Section: Discussionmentioning
confidence: 98%